STRENGTHENING EMOTIONAL INTELLIGENCE AND NURSE PERFORMANCE AT RSUD DR. DRAJAT PRAWIRANEGARA - Prahiawan, Wawan; Mariska, Tika; Damarwulan, Liza M (Management Science Research Journal, 2022)
Performance is an important thing that reflects the good or bad service of an institution. This research was conducted at RSUD Dr. Drajat Prawiranegara to find out how the influence of emotional intelligence in improving employee performance by using the intervening variable of work discipline. The research population was 83 nurses. This study is a causality study whose data were analyzed using the SEM-PLS method. Based on the hypothesis test conducted, it shows that there is a positive and significant effect of emotional intelligence on work discipline and employee performance, and there is a positive and significant effect of work discipline on the performance at RSUD Dr. Prawiranegara Drajat. This study also proves that there is a partial mediation of work discipline on the influence of emotional intelligence to improve employee performance.